2022
DOI: 10.3390/en16010020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermopressor with Incomplete Evaporation for Gas Turbine Intercooling Systems

Abstract: One of the promising ways to increase fuel and modern gas turbine energy efficiency is using cyclic air intercooling between the stages of high- and low-pressure compressors. For intercooling, it is possible to use cooling in the surface heat exchanger and the contact method when water is injected into the compressor air path. In the presented research on the cooling contact method, it is proposed to use a thermopressor that implements the thermo-gas-dynamic compression process, i.e., increasing the airflow pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Additionally, it was shown that the positive effect gained due to thermo-gas-dynamic compression in the thermopressor is greater, and the friction loss is smaller. Losses due to friction according to the classical method of calculation are up to 5-8 % [41,42]. Therefore, a substantial portion of present research is dedicated to the development of a methodology for calculating pressure losses, affected by design parameters, with specific attention to the resistance of the thermopressor confuser and diffuser.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, it was shown that the positive effect gained due to thermo-gas-dynamic compression in the thermopressor is greater, and the friction loss is smaller. Losses due to friction according to the classical method of calculation are up to 5-8 % [41,42]. Therefore, a substantial portion of present research is dedicated to the development of a methodology for calculating pressure losses, affected by design parameters, with specific attention to the resistance of the thermopressor confuser and diffuser.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Iron losses at the desired load point are determined from the no-load curve at voltage V i reduced by the ohmic voltage drop in the primary winding: P fe = P 0 − P S0 − P fw . (6) Losses in the stator winding depend on the load P s .…”
Section: Test Procedures and Conditionsmentioning
confidence: 99%
“…Designing an effective cooling system for these motors is crucial, as it directly impacts their reliability, efficiency, and overall functionality [3,4]. This requires a comprehensive understanding of the technical demands and challenges associated with motor cooling [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The excessive heat of return hot water, not consumed by ACh, is removed to the atmosphere through discharge radiator. The refrigerant ejector chiller (ECh) [37,38] of jet type [39,40] might be easy implemented as a booster stage of absorption-ejector type chiller (AECh) to convert the excess heat left behind the ACh [41,42] for cooling the air sucked by engine [43,44].…”
Section: Introductionmentioning
confidence: 99%